Assessment of the willingness to pay for the protection of the algodonal river - Rodríguez Suarez, Alex Mauricio (Universidad Francisco de Paula Santander, 2016)
This paper aims to identify the willingness to pay of the inhabitants of Ocaña for the conservation of the ecosystem services provided by the Algodonal River basin, for this purpose, in the introduction, a conceptual framework of the environmental economy is designed to establish the role of the government as the main responsible for the protection of natural resources, then using the methodology of the logical framework a current description of the river basin is made that allows to identify the problems, causes and consequences, in order to propose an alternative of preservation in the basin , finally define the main variables of the contingent valuation model that allows establishing the willingness to pay of the Ocaña citizensas a financing strategy